Methodological basis for forming youth policy management at university within the framework of public administration theory - D. L. Ostrovkin; D. G. Sandler (Вестник университета)
Theoretical analysis of the youth policy at university concept within the framework of the public administration theory has been carried out. The purpose of the study is to substantiate the methodological approach to building a model of youth policy implementation management at university. Different approaches to the youth policy definition in Russian and foreign scientific literature, as well as in the public administration theory have been considered. The ways of youth policy development considering the stakeholder approach have been investigated. The authors’ vision of the essence of the youth policy in higher education institution concept in the context of strategic development of higher education system has been proposed. The principles of youth policy formation based on the matrix model have been developed, according to which the solution of youth issues should be accompanied by the integration of the policy elements in all strategies, programs, and projects at different levels of university management. A methodological approach based on the subject-object paradigm has been proposed, which contributes to creating a sustainable model of youth policy development at university. This approach is aimed at strengthening the importance of youth policy and includes tasks that increase an educational organization competitiveness.